Pembuatan Bakso Ikan Toman (Channa micropeltes) / Making Meatball of Toman Fish (Channa micropeltes) - Restu Restu (Fakultas Peternakan Universitas Kristen Palangka Raya, 2012)
Processing of fishery products are generally intended to preserve freshness, preserve, create a product that has physical and chemical properties are different than the original, but still frowned upon by society. Fish ball (Bakso) is the result of fish processing is done by mixed fish meat that has been crushed / milled with tapioca flour and spices, formed spheres (balls), then boiled / steamed at a temperature of 90 ± 2 ° C for 30 minutes. The research goal to determine the composition of tapioca in order to obtain compact meatballs with the ideal flavor, and have good nutritional value for consumers. The best results were based on proximate analysis and organoleptic tests on toman fish meatball product, obtained in the treatment of the B by nutritional value: carbohydrate 16.5%, protein 10.92%, fat 1.2%, and 70.4% water. and organoleptic value of 7.2 (hedonic scale). The resulting specification meatball (appearance) is clean and attractive, distinctive odor attractive meatball taste, unique flavor of fish meatballs and delicious, and quite firm and compact.